O15.6 Differences in reported testing barriers between clients of an online sti testing service (getcheckedonline.com) and a provincial sti clinic in vancouver, canada. (8th July 2017) - Gilbert, Mark; Thomson, Kimberly; Hottes, Travis; Haag, Devon; Carson, Anna; Grennan, Troy; Fairley, Christopher; Kerr, Thomas; Buchner, Chris; Krajden, Mel; Kendall, Perry; Ogilvie, Gina; et al.
Abstract : Introduction: Online STI testing programs are thought to overcome barriers posed by in-clinic testing, though uptake could reflect social gradients (e.g., technology access, higher education). To understand types of barriers mitigated by online STI testing we compared clients of a large STI clinic to clients of GetCheckedOnline (GCO). Methods: Our study was conducted in Vancouver after GCO was promoted to provincial STI clinic clients and men who have sex with men (MSM). Clinic and GCO clients were invited to an online survey 2 weeks after receiving test results. Survey questions included barriers/facilitators of testing at individual, provider, clinic and societal levels. We conducted bivariate comparisons between groups (significant results shown at p<0.01). Results: GCO (n=87) were older than clinic clients (n=424; median 35 vs. 31 years) and a higher proportion were MSM (40.2% vs. 24.4. More GCO clients reported their reason for testing as routine (58.1% vs. 38.9%) and fewer for symptoms or STI contact (10.3% vs 33.5%). More GCO clients considered accessing online health resources important (76.1% vs 56.5%) but otherwise did not differ on technology skills/use. GCO clients were more likely to report delaying testing in the past year due to clinic distance (22.4% vs 9.7%), less likely to agree that clinic hours were convenient (58.2% vs 77.2%) or that making appointments was easy (49.4% vs. 65.4%), and more likely to report long wait times to see a health care provider (HCP) (47.6% vs 20.7%). GCO clients were more likely to be uncomfortable discussing their sexual history with HCP in general (15.5% vs 5.7%) and where they usually presented for health care (34.9% vs 20.6%), as well as reporting more fear of being judged by HCP (28.6% vs 15.4%). Conclusion: Our study in Vancouver suggests that online testing services may effectively engage individuals with barriers to testing (i.e., clinic access, discomfort with HCP) with few social gradients in uptake. Further evaluation to verify these findings within different cities/populations is needed.